2017
DOI: 10.1002/chem.201703967
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Structures of Uranyl–Tri‐n‐butyl‐Phosphate Aggregates by Coupling Experimental Results with Molecular Dynamic Simulations

Abstract: The complex structure of a plutonium uranium refining by extraction (PUREX) process organic phase was characterized by combining results from experiments and molecular dynamics simulations. For the first time, the molecular interactions between tri-n-butyl phosphate (TBP) and the extracted solutes, as well as TBP aggregation after the extraction of water and/or uranyl nitrate, were described and analyzed concomitantly. Coupling molecular dynamics simulations with small- and wide-angle X-ray scattering (SWAXS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…This is because the coordination numbers used for calculations were found at 40 vol.% of TBP concentration. It is known also that TBP can form aggregates in applied separations, which lead sometimes to the formation of a third phase [31,32].…”
Section: LImentioning
confidence: 99%
“…This is because the coordination numbers used for calculations were found at 40 vol.% of TBP concentration. It is known also that TBP can form aggregates in applied separations, which lead sometimes to the formation of a third phase [31,32].…”
Section: LImentioning
confidence: 99%
“…we assumed that number since, according to ref. 84, most efficient extraction systems have local water in the oil cylindrical microstructure, with both the typical cylinder diameter and length per extracted ion in the order of one nanometre. From this, the number of complexing molecules in the first and second coordination positions can easily be calculated to be between eight and ten.…”
Section: Study Of the Parameters Influencing The Extraction Propertiesmentioning
confidence: 99%
“…10 shows the observed free energies of transfer in the dilute phase (light yellow), which range between BÀ0.5 and À1.5 kJ mole À1 . Regarding the third phase (orange), made of interconnected polar cylinders, 84 Gibbs free energy is too strong to be measured with ion concentrations in the organic phase that are too low to be measured (hence free energies of transfer values diverge, which we represented with arrows pointing down going all the way).…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…[8][9][10][11] In the liquid-liquid solvent extraction system, it is predicted that uranyl ion complexes with TBP form UO 2 $NO 3 $4TBP, UO 2 $5TBP and UO 2 $NO 3 -$3TBP$HNO 3 in the interface or in the organic phase. 12 Guilbaud et al 13 reported the aggregation of UO 2 (NO 3 ) 2 (TBP) 2 at a high uranium concentration. As for a supercritical CO 2 extraction system, only Wipff et al 14,15 investigated the complexation of uranyl nitrate with TBP at the interface of the supercritical CO 2 /aqueous phase.…”
Section: Introductionmentioning
confidence: 99%